Economic Crisis and Hajj Registration Cancellation after Covid-19: A Socio-Legal Analysis of Rational Choice and Fiqh Priority in Jember - Ahmadiono; Sofkhatin Khumaidah (Sharia Faculty, Kiai Haji Achmad Siddiq State Islamic University of Jember, 2026)
The Covid-19 pandemic triggered a severe economic crisis that significantly affected the legal and social capacity of Indonesian Muslims to fulfill religious obligations, particularly the performance of hajj. In Jember Regency, a substantial number of registered hajj pilgrims cancelled their hajj registration by withdrawing the initial deposit due to economic hardship during and after the pandemic. This study aims to analyze the phenomenon of hajj registration cancellation from a socio-legal perspective by examining the rational considerations of pilgrims and their normative justification within Islamic law, particularly through rational choice theory and fiqh al-awlawiyyat (jurisprudence of priorities). This research employs a qualitative field approach with a phenomenological method. Data were collected through in-depth interviews, observation, and documentation involving pilgrims who cancelled their hajj registration as a result of pandemic-related economic disruption. The findings demonstrate that declining household income caused by the death of family breadwinners, disrupted business cash flow, and a sharp decrease in small-scale enterprise revenues constituted the primary factors behind hajj cancellation. Faced with urgent legal and moral obligations such as debt repayment, employee wages, and daily subsistence needs, pilgrims made rational decisions to prioritize immediate necessities over maintaining their hajj quota. From the perspective of Islamic law, this decision aligns with the principle of fiqh priority, which emphasizes the fulfillment of human rights and obligations before performing acts of worship related to the rights of God. This study contributes to socio-legal scholarship by illustrating how economic rationality, legal consciousness, and Islamic normative reasoning interact in shaping religious decision-making during times of crisis.